Subjective Responses to Translation Memory Policy in the Workplace - Mossop, Brian (TTR)

(untitled) (Association canadienne de traductologie, 2019)
The gradual introduction of Translation Memory in translation workplaces, starting in the late 1990s, has created a classic industrial conflict. Managers and clients of translation services want to increase productivity, but translators do not want to be told how to produce translations, and they do not want to see their incomes reduced. While the technical features of Memory programs certainly cause dissatisfaction, all technologies have defects, and a key question then is who decides how to deal with these defects—translators? or managers and clients? As a result, policies on the use of Memory in a workplace become crucial. There are objective policy questions: Are translators’ productivity requirements increased when Memory is introduced? Do translators receive less pay for matches found in the Memory database? Is the translator allowed to search the Memory database? Then there is the subjective aspect: how do translators feel about their own experience of whatever is objectively happening? Do they feel they are in control of the texts they are producing? Are technologies increasing or decreasing their satisfaction with their working lives? Do they have a sense of losing the ability to compose their own translations or are they equally happy to revise wordings proposed by Memory? Do they feel that use of these technologies is reducing or enhancing the status of translators in society? This article looks at some of these subjective matters, based on two surveys of Ontario translators conducted in 2011 and 2017.